2019
DOI: 10.1016/j.carbpol.2018.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Probing adhesion between nanoscale cellulose fibres using AFM lateral force spectroscopy: The effect of hemicelluloses on hydrogen bonding

Abstract: Highlights  Developed an AFM technique to probe adhesion in cellulose-based networks.  Characterized the nanoscale adhesion forces between cellulose fibres.  Assessed the effect of xyloglucan and arabinoxylan on nano-scale adhesion forces.  Provided insights into the effect of xyloglucan on cellulose-cellulose adhesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(7 citation statements)
references
References 79 publications
(103 reference statements)
1
6
0
Order By: Relevance
“…The micromechanics of the gel fibers measured by AFM (Figure ) shows that for individual fibers or bundles of fibers, there is no significant difference in the mechanical properties of the BC, BC–AX, and BC–XG gels ( p > 0.05). This finding is in agreement with recent AFM studies using “drag-and-dip” lateral force AFM experiments to probe adhesive forces and micromechanics of BC composites, which produced results suggesting that BC, BC–AX, and BC–XG have very similar micromechanical properties . Our observation that MLG significantly reduces the stiffness of cellulose fibers has, to the best of the authors’ knowledge, not been previously reported .…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The micromechanics of the gel fibers measured by AFM (Figure ) shows that for individual fibers or bundles of fibers, there is no significant difference in the mechanical properties of the BC, BC–AX, and BC–XG gels ( p > 0.05). This finding is in agreement with recent AFM studies using “drag-and-dip” lateral force AFM experiments to probe adhesive forces and micromechanics of BC composites, which produced results suggesting that BC, BC–AX, and BC–XG have very similar micromechanical properties . Our observation that MLG significantly reduces the stiffness of cellulose fibers has, to the best of the authors’ knowledge, not been previously reported .…”
Section: Resultssupporting
confidence: 93%
“…This finding is in agreement with recent AFM studies using "drag-and-dip" lateral force AFM experiments to probe adhesive forces and micromechanics of BC composites, which produced results suggesting that BC, BC−AX, and BC−XG have very similar micromechanical properties. 36 Our observation that MLG significantly reduces the stiffness of cellulose fibers has, to the best of the authors' knowledge, not been previously reported. 9 More generally, the discrepancy between AFM-based and rheological data on the BC−MLG gels may simply reflect the fact that the AFM indentation experiments probe only the region at and immediately beneath the gel surface, whereas the rheological experiments reflect the behavior of a much deeper section (as shown by their dependence on the gel thickness).…”
Section: ■ Results and Discussionmentioning
confidence: 53%
“…and, potentially, higher cellulose surface coverage. Such configuration would result in more open pores and at the same time it would reduce the formation of direct adhesive links between cellulose fibrils, thereby preserving the compliant nature of the BC network 48 . For all hydrogels, we observed a marked difference between the E relax and G', which may be explained by considering material anisotropy.…”
Section: Resultsmentioning
confidence: 99%
“…For BC-AGX composites, which show high permeability while being mechanically more compliant, it is possible to suggest that AGX adsorbs onto cellulose fibrils with fewer “dangling segments” and ‘“loops,” and, potentially, higher cellulose surface coverage. Such configuration would result in more open pores and at the same time it would reduce the formation of direct adhesive links between cellulose fibrils, thereby preserving the compliant nature of the BC network 48 .…”
Section: Resultsmentioning
confidence: 99%
“…To quantify this cohesion, we have studied the adhesion between CNF and AgNWs at the microscopic scale by AFM. We have chosen AFM to probe this adhesion because it has led to successful measurements of the mechanical properties of nanowires or nanofibers [33][34][35].…”
Section: Nanoscale Resultsmentioning
confidence: 99%